(untitled) (Journal of Face Aesthetics, 2024)
The Department of Development Poznań Dentistry – DRPS, as young employees called “drops”, was established in September 1991 by a 10-person initiative group, originating from the scientific and teaching staff of the Institute of Dentistry of the Medical Academy in Poznań – today the Karol Marcinkowski Poznań Medical University in Poland.